EKSISTENSI DAN PROBLEMATIKA DAKWAH DI TENGAH PANDEMI COVID-19 - Parhan, Muhamad; Khairulimam, Abizar; Nurfitriyani, Mita; Ababil, Salza Nabila (Jurnal Dakwah Tabligh, 2021)
This research is motivated by the presence of the COVID-19 outbreak, which causes many activities that cannot be done by gathering and meeting face to face. This impact is not only in the world of business or education, but also has an impact on worship activities and other religious activities such as congregational prayer at the mosque, weekly recitation at the mosque, including listening to da'wah directly from the ulama. With the COVID-19 outbreak as a pandemic that has spread to various countries, another step is needed in religious activities to prevent and break the COVID-19 chain so that it does not spread widely. So staying at home and maintaining a distance is the choice of Muslims when circumstances are felt to be detrimental to themselves and others. In response to this, it is necessary to conduct a study of some of the impacts that occur in da'wah activities in the middle of a pandemic, which aims to find out whether due to the many obstacles, da'wah activities are still being carried out or not. To achieve this goal, this study used a qualitative-descriptive research method with literature study techniques. The result of this study obtained data and the fact that there are many problems in da'wah in a pandemic situation like this. However, the data shows that the problems that occur are not a barrier to the existence of da'wah amid the COVID-19 pandemic